Hubungan antara Dukungan Sosial Orang Tua dengan Penyesuaian Diri Mahasiswa Baru yang Merantau - Maria Stephanie Gunandar; Muhana Sofiati Utami (Gadjah Mada Journal of Psychology (GamaJoP), 2017)
Adjustment in the freshmen students that leaving home for college is a process for an individual facing changes and learning to fit in with a new environment. The aim of the study is to determine the correlation between parental social-support with adjustment of the freshmen that leaving home for college. The subjects of the study are 96 undergraduates grade 2016 from several faculties of Universitas Gadjah Mada, they are Psychology, Economics, and Business, also Social and Politics. Subjects are chosen by using purposive sampling method. Product Moment correlation analysis showed that there was an association between parental social support with adjustment of the freshmen that leaving home for college with 0,317 as the correlation score. There was a positive and significant correlation between parental social-support with adjustment of the freshmen that leaving home for college.